Juridical Review of Traffic Accident Crimes Involving Pedestrians as Perpetrators at the Klungkung Police Resort - Sihotang, Erikson; Rupini, Luh Made Ayu; Suandika, I Nyoman (Ridwan Institute, 2026)
Traffic accidents are not always caused by the driver of a motor vehicle; under certain conditions, they can also involve pedestrians as perpetrators. This phenomenon raises its own legal problems, especially in the process of determining perpetrators and applying criminal liability by law enforcement officials. This study aims to examine the determination of pedestrians as perpetrators of traffic accidents and to analyze law enforcement in these cases within the jurisdiction of the Klungkung Resort Police. It employs a normative juridical method supported by an empirical approach, with legislative and conceptual approaches. The data were analyzed based on the provisions of the Criminal Code, the Criminal Procedure Code, and Law Number 22 of 2009 concerning Road Traffic and Transportation, associated with field investigation practices. The results show that the determination of pedestrians as perpetrators of traffic accidents is based on the principle of negligence (culpa), with fulfillment of the elements of error and valid proof. Law enforcement against pedestrians as perpetrators of traffic accidents at the Klungkung Resort Police is carried out professionally by prioritizing evidence, prudence, and a restorative justice approach. This research emphasizes the importance of investigators' meticulousness in assessing the elements of error to avoid improper criminalization and ensure legal certainty and justice.